Stakeholders’ Perception of Safety Prioritization at Ship Services in the Sunda Strait - Anwar, Khoirul (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2019)
The role of shipping safety in the sea transportation system is absolutely calculated. Shipping safety concerns the transportation of goods and people crossing the ocean in full danger and the threat of storms, fog and movements and seas such as waves, currents, sea corals, siltation and fixed and changing shipping lanes, making sea transportation in shipping at high risk. This study aims to 1) Know the variables that affect the level of safety of the Roak Ro-Roakeuni Ro-Ro Crossing Ship; 2) Analyzing the level of safety of transportation safety from the Sunda Strait. Methods of collecting data directly in the field and collecting secondary data. The results of the study show that the variables that affect ship safety include infrastructure, facilities and culture. The most influential factor on ship safety in the Sunda Strait is a cultural factor. Based on the results of the safety safety analysis, the Sunda Strait has a high level of vulnerability due to the density of ship traffic and the lack of Aids to Navigation in the Sunda Strait.